Correlates of recent HIV testing among transgender women in Greater Kuala Lumpur, Malaysia - Rutledge, Ronnye; Morozova, Olga; Gibson, Britton A.; Altice, Frederick L.; Kamarulzaman, Adeeba; Wickersham, Jeffrey A. (Mary Ann Liebert, 2018)
Purpose: In Malaysia, an estimated 9.7%-12.4% of transgender women (TW) are HIV positive, with higher estimates among those engaged in sex work. According to the 90-90-90 Joint United Nations Programme on HIV/AIDS strategy, HIV testing is the first crucial step in curbing the HIV epidemic. This study examines correlates of recent HIV testing among TW in Greater Kuala Lumpur, Malaysia. Methods: TW (N = 199) in Greater Kuala Lumpur completed a survey on healthcare access and utilization, including HIV testing history. Bivariate logistic regression and penalized multivariate logistic regression were used to explore correlates of HIV testing in the last 12 months. Results: Overall, 41.7% of TW reported having ever been tested for HIV. Among participants who were HIV negative or not sure of their HIV status (n = 187), only 18.7% (n = 35) had been tested for HIV in the last 12 months. The multivariate analysis indicated that having a primary care provider (PCP), being 26-40 years of age, and having higher mental health functioning were positively associated with recent HIV testing. Active amphetamine use and previous depression diagnosis were also associated with recent HIV testing. Conclusion: HIV testing is the first step in linking individuals to prevention and treatment interventions. Our findings suggest that having a PCP can improve engagement in HIV testing. Moreover, PCPs can serve as a valuable link to HIV treatment and prevention services. Current interventions that target social and behavioral risk factors for HIV, on their own, may be insufficient at engaging all HIV-vulnerable TW.